2016
DOI: 10.1039/c6ra05045j
|View full text |Cite
|
Sign up to set email alerts
|

Novel photo-curable polyurethane resin for stereolithography

Abstract: A novel photo-curable polyurethane resin for stereolithography has been demonstrated herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Recently, 3D printing methods have received signicant attention for their application in rapid prototyping, electronics, microuidics, and tissue engineering. [1][2][3][4][5][6][7][8][9][10] The possibility of constructing unusual and complex structures drawn via computer-aided design (CAD) is the reason we are interested in this technology. Several approaches exist for additive manufacturing technology, including fused deposition modelling (FDM), selective laser sintering (SLS), stereolithography (SLA), and inkjet 3D printing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 3D printing methods have received signicant attention for their application in rapid prototyping, electronics, microuidics, and tissue engineering. [1][2][3][4][5][6][7][8][9][10] The possibility of constructing unusual and complex structures drawn via computer-aided design (CAD) is the reason we are interested in this technology. Several approaches exist for additive manufacturing technology, including fused deposition modelling (FDM), selective laser sintering (SLS), stereolithography (SLA), and inkjet 3D printing.…”
Section: Introductionmentioning
confidence: 99%
“…Tough 3D printed photopolymers are particularly useful in the fabrication of durable load-bearing structures with tailored geometries and physical properties such as implantable devices and biological scaffolds. [16,17] These materials demand a good combination of strength and ductility that is comparable with natural tissues such as muscle and tendon.…”
mentioning
confidence: 99%
“…Attempts on toughening 3D printed polyacrylate-based resins have been conducted using typical fillers such as graphene oxide (GO), [18] siloxanes, [17,19,20] and ceramics [21,22] to form composites. For instance, the study of functionalized GO/methacrylate nanocomposites by Palaganas et al [18] showed an overall improvement on strength, ductility, and toughness at 0.2% GO content compared to unfilled methacrylate resin.…”
mentioning
confidence: 99%
“…5 Le Hoang Sinh et al demonstrated a novel photo-curable polyurethane resin for stereolithography, which could accurately and precisely simulate articial skin blood vessel model. 6 There are few reports on the application of resins combined with UV-curing 3D molding technology to obtain degradable materials for anti-biofouling. In our previous work, a cross-linked network of functionalized poly(L-lactic) (PLLA) with NVP was developed for application in the eld of antifouling.…”
Section: Introductionmentioning
confidence: 99%